An overview of anti-Hepatitis B virus flavonoids and their mechanisms of action - Naderi, Malihe; Salavatiha, Zahra; Gogoi, Urvashee; Mohebbi, Alireza (Frontiers in Cellular and Infection Microbiology, 2024)
Flavonoids, a diverse group of polyphenolic compounds found in various plant-based foods, have garnered attention for their potential in combating Hepatitis B Virus (HBV) infection. Flavonoids have demonstrated promising anti-HBV activities by interfering with multiple stages of the HBV life cycle, making them promising candidates for novel antiviral agents. Certain plant families, such as Theaceae, Asteraceae, Lamiaceae, and Gentianaceae, are of particular interest for their flavonoid-rich members with anti-HBV activities.Evidences, both in vitro and in vivo, supports the anti-HBV potential of flavonoids. These subsets of compound exert their anti-HBV effects through various mechanisms, including inhibiting viral entry, disrupting viral replication, modulating transcription factors, enhancing the immune response, and inducing autophagy. The antioxidant properties of flavonoids play a crucial role in mitigating oxidative stress associated with HBV infection. Several flavonoids like EGCG, PAC, hexamethoxyflavone, wogonin, and baicalin have shown significant anti-HBV potential, holding promise as therapeutic agents. Synergistic effects between flavonoids and existing antiviral therapies offer a promising approach to enhance antiviral efficacy and reduce drug resistance.Challenges, including limited bioavailability, translation from preclinical studies to clinical practice, and understanding precise targets, need to be addressed. Future research should focus on clinical trials, combination therapies, and the development of flavonoid derivatives with improved bioavailability, and optimizing their effectiveness in managing chronic HBV infections.